(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The ultimate goal of this study is to enhance the cultural competence of the Syrian students at both the school and university phases throughout the teaching of English. The first part of this study provides what many researchers think about the roles of the textbook and the teacher in strengthening the relationship between the learner and his/her own culture and/or the other cultures including the target culture. In the second part of this study, an analysis from a cultural perspective of the Syrian context is provided. This analysis focuses on the English language textbooks used at the Syrian schools and at Tishreen university. Then it moves to both the Syrian teachers and leaners. The last part of this study gives some suggestions that could be helpful in strengthening the cultural awareness in the Syrian educational system.